The impact of Korra tef (Eragrostis tef) adoption on commercialization status of tef producing farmers in Northwestern Ethiopia: A propensity score matching analysis - Solomon Zewdu Leul; Alemu Azmeraw Bekele; Alemseged Gerezgiher Hailu; Solomon Tsehay Feleke (Cogent Economics & Finance, 2023)
The government and other development practitioners in Ethiopia have promoted crop technologies like improved tef varieties to improve crop productivity of farmers and, in turn, their commercialization status. The commercialization impacts of these crops, however, were not thoroughly examined. This study examined the commercialization impact of adopting improved tef variety (Korra) in North-western Ethiopia using cross-sectional data of 479 tef producer farm households drawn from two districts, one from the adopters and the other from non-adopters. A multi-stage sampling procedure was followed to select the respondents. A semi-structured questionnaire was used as a principal primary data collection method to collect household survey data, and interviews were conducted with the relevant key informants of the study. The extent of smallholder commercialization was examined using the Household Commercialization Index (HCI), and the impact of Korra tef adoption on adopters' commercialization was estimated using Propensity Score Matching (PSM). The HCI result revealed that 46.95% of sampled farmers sold tef during 2020; while it was 58.92% and 36.7% for the adopters and non-adopters, respectively. This indicated that the non-adopters and adopters were, respectively, semi- and commercialized. The PSM result also revealed a positive and significant impact on households' tef commercialization, with the adopters' commercialization rate exceeding the non-adopters by about 23.43%. Hence, efforts should focus on ensuring that farmers have access to sufficient quantities of high-quality improved Korra tef seed as well as encouraging improved access to institutional services for the same.
Keywords: 330; adopters; Agricultural Growth Program II; household commercialization index; impact assessment; Korra tef; non-adopters